Two predicted α-helices within the prion-like domain of TIAR-1 play a crucial role in its association with stress granules in Caenorhabditis elegans - Fuentes-Jiménez, D. A.; Salinas, L. S.; Morales-Oliva, E.; Ramírez-Ramírez, V. A.; Arciniega, M.; Navarro, R. E. (Frontiers in Cell and Developmental Biology, 2023)
Stress granules (SGs) are sites for mRNA storage, protection, and translation repression. TIA1 and TIAR1 are two RNA-binding proteins that are key players in SGs formation in mammals. TIA1/TIAR have a prion-like domain (PrD) in their C-terminal that promotes liquid-phase separation. Lack of any TIA1/TIAR has severe consequences in mice. However, it is not clear whether the failure to form proper SGs is the cause of any of these problems. We disrupted two predicted α-helices within the prion-like domain of the Caenohabditis elegans TIA1/TIAR homolog, TIAR-1, to test whether its association with SGs is important for the nematode. We found that tiar-1 PrD mutant animals continued to form TIAR-1 condensates under stress in the C. elegans gonad. Nonetheless, TIAR-1 condensates appeared fragile and disassembled quickly after stress. Apparently, the SGs continued to associate regularly as observed with CGH-1, an SG marker. Like tiar-1-knockout nematodes, tiar-1 PrD mutant animals exhibited fertility problems and a shorter lifespan. Notwithstanding this, tiar-1 PrD mutant nematodes were no longer sensitive to stress. Our data demonstrate that the predicted prion-like domain of TIAR-1 is important for its association with stress granules. Moreover, this domain may also play a significant role in various TIAR-1 functions unrelated to stress, such as fertility, embryogenesis and lifespan.